Hedging in News Stories and Editorials in The Jakarta Post and The Washington Times - Ardi Nugroho (Universitas Bunda Mulia, 2017)
The use of hedges in academic discourse is important because academic writers need to present their findings and arguments accurately but carefully so that they are academically appropriate. Many researches have been conducted on this topic; however, not many studies have explored the use of hedges in other discourses such as newspaper discourse. Newspapers contain different types of articles with different linguistic characteristics. These different characteristics may include the different uses of hedges. The use of hedges in newspapers is no less important as their use in academic discourse, as newspapers serve as an important source of information. This research is an attempt to find out the frequency and the different types of hedges used in two newspapers, i.e. The Jakarta Post and The Washington Times newspaper. The types of articles that are used as the object of study are news stories and editorials. This study also compares the use of hedges in the two types of articles from both newspapers. The findings show that hedges are used more frequently in editorials compared to news stories in both newspapers. However, the Indonesian writers tend to use hedges more frequently compared to the American writers, especially in news stories. Keywords: hedges, news stories, editorials